2021
DOI: 10.1111/php.13505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TEOA on the Process of Photopolymerization at 532 nm and Properties of Nanogels

Abstract: Nanogel is an important kind of biomaterials applied for wound dressings, drug delivery, medical diagnostics and biosensors. The properties of nanogels closely depend on the density of the crosslinking network. In this study, the role of triethanolamine (TEOA) in the effect on the crosslinking degree of nanogels based on poly(ethylene glycol) diacrylate (PEGDA) was investigated and illustrated. The effect of TEOA on the process of photopolymerization at 532 nm and properties of the nanogels was systematically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…It was suggested that the increase in the molar ratios of activated phenylboronic acid groups from pba‐ePL or hydroxyl groups from tannic acid would cause less efficient crosslinking and decrease the crosslinking degree, leading to larger NGs. [ 25 ] Thus, NGs at the moderate P/T ratios of 5/1 and 10/1 were chosen in the subsequent experiment. In addition, all NGs exhibited negative zeta potentials from −16 to −20 mV (Figure 1i).…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that the increase in the molar ratios of activated phenylboronic acid groups from pba‐ePL or hydroxyl groups from tannic acid would cause less efficient crosslinking and decrease the crosslinking degree, leading to larger NGs. [ 25 ] Thus, NGs at the moderate P/T ratios of 5/1 and 10/1 were chosen in the subsequent experiment. In addition, all NGs exhibited negative zeta potentials from −16 to −20 mV (Figure 1i).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Bakó prepared nanogels using methacrylic acid poly-γ-glutamic nanoparticles loading antibiotic drug ampicillin by visible (blue) light-initiated photopolymerization, and the release kinetics showed the controlled and efficient release behaviors (Bakó et al, 2016). Notably, our lab has also developed some strategies on the preparation of nanogels through laser photopolymerization, which is related with the investigation of the initiating system, polymerization mechanism and biomedical applications (Li J. et al, 2021;Liu et al, 2021;Peng et al, 2021;Wang et al, 2021). Specifically, Wang chose biocompatible polyethylene glycol diacrylate (PEGDA) as a monomer and ultrasmall nanogels with around 30 nm in size were prepared successfully through surfactant-free photopolymerization at 532 nm.…”
Section: Free Radical Polymerizationmentioning
confidence: 99%
“…[5][6][7][8] Many kinds of cross-linked host matrices have been reported, which are a mixture of at least two active substances, such as epoxy-amine, epoxy-thiol, isocyanate-alcohol, orthoester-anhydride, and thiol-allyl. [9][10][11][12][13][14] Compared with other cross-linked systems, epoxy-amine has excellent mechanical properties and low volume shrinkage, which is very important for millimeter-thick media in holographic data storage. However, high cross-linking density of epoxyamine matrices sacrificed the diffusivity of monomers, resulting in blurry grating fringes of allyl/epoxy-amine-based photopolymers, which limited their further applications.…”
Section: Introductionmentioning
confidence: 99%